Exploiting Rye in Wheat Quality Breeding: The Case of Arabinoxylan Content - Maria Chiara Piro; Hilde Muylle; Geert Haesaert (Plants, 2023)
Rye (Secale cereale subsp. cereale L.) has long been exploited as a valuable alternative genetic resource in wheat (Triticum aestivum L.) breeding. Indeed, the introgression of rye genetic material led to significant breakthroughs in the improvement of disease and pest resistance of wheat, as well as a few agronomic traits. While such traits remain a high priority in cereal breeding, nutritional aspects of grain crops are coming under the spotlight as consumers become more conscious about their dietary choices and the food industry strives to offer food options that meet their demands. To address this new challenge, wheat breeding can once again turn to rye to look for additional genetic variation. A nutritional aspect that can potentially greatly benefit from the introgression of rye genetic material is the dietary fibre content of flour. In fact, rye is richer in dietary fibre than wheat, especially in terms of arabinoxylan content. Arabinoxylan is a major dietary fibre component in wheat and rye endosperm flours, and it is associated with a variety of health benefits, including normalisation of glycaemic levels and promotion of the gut microbiota. Thus, it is a valuable addition to the human diet, and it can represent a novel target for wheat–rye introgression breeding.